NEW DIGGING WORKING BODY FOR ROOT POTATO HARVESTER - Грушецький, С. М.; Збаравська, Л. Ю.; Семенишина, І. В.; Скоробогатов, Д. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
Ukraine has a unique natural potential, which allows it to become a leader in the production of agricultural products in Europe. However, for successful entry into the western markets, it is necessary to ensure, first of all, the competitiveness of its own products, which can be achieved by the complex mechanization of technological processes, reducing labor costs, increasing yields and quality of the received products. A new digging body for root harvesters was proposed in terms of the modern technology of cultivating and harvesting potatoes, which would collect both the minimum amount of soil and the tubers and ensure the better furrow slice fragmentation to facilitate separation in terms of increased operational efficiency, technological reliability of the digging working body and reduction of drawing resistance. Investigation of the problem of improving the existing and the invention of up-to-date working bodies of potato harvesting equipment, justification of optimal modes of their work and, as a result, providing this crop sector with modern, highly-efficient and reliable harvesting equipment. Theoretical analysis of psychological and educational literature on research with a view to the selection and interpretation factual material; analysis of concepts, theories and techniques was aimed to identify ways of solving problems studied closest to students' future careers. The result of the study is the identification of advanced ways to improve the digging working bodies for root potato harvesters. Technological and economic indicators of advanced potato harvesting technologies are determined